2018
DOI: 10.1017/jfm.2018.461
|View full text |Cite
|
Sign up to set email alerts
|

Flat plate impact on water

Abstract: While the classical problem of a flat plate impact on a water surface at zero dead-rise angle has been studied for a long time both theoretically and experimentally, it still presents a number of challenges and unsolved questions. Hitherto, the details of the flow field – especially at early times and close to the plate edge, where the classical inviscid theory predicts a singularity in the velocity field and thus in the free surface deflection, so-called ejecta – have not been studied experimentally, which le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 52 publications
8
27
0
Order By: Relevance
“…Similar observations have been made for squeeze flows between a solid and a fluid phase in several previous studies [90,91,93,100,101,102,103,104,105]. Mayer & Krechetnikov [78] estimated the thickness of a trapped air layer by impacting thin, flat plates on water, while Hicks et al [90] performed calculations for a shallow, convex surface impacting on water. In both works, the thickness of trapped air layer, and the extent of FS being pushed down were of similar magnitude (∼ O(10 2 µm)) to what we show in figures 2.2 and 2.3.…”
Section: First Observationssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar observations have been made for squeeze flows between a solid and a fluid phase in several previous studies [90,91,93,100,101,102,103,104,105]. Mayer & Krechetnikov [78] estimated the thickness of a trapped air layer by impacting thin, flat plates on water, while Hicks et al [90] performed calculations for a shallow, convex surface impacting on water. In both works, the thickness of trapped air layer, and the extent of FS being pushed down were of similar magnitude (∼ O(10 2 µm)) to what we show in figures 2.2 and 2.3.…”
Section: First Observationssupporting
confidence: 65%
“…The physics of liquid impacts has received a substantial amount of attention over a long period of time [74]. Post-impact phenomena in particular, such as the resulting fluid flows [75,76,77,78,79,80,81], and issues of more practical importance such as structural loads caused by the impact have been exhaustively studied [22,27,82,83,84,85,86,87,88]. However, many phenomena depend crucially on what happens immediately before the moment of impact, when the ambient fluid (usually air) plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained as follows: the closer the pressure measuring point is to the edge of the plate, the more easily the wave breaks up, and complex conditions occur. In this circumstance, the compressibility of air bubbles, and even hydro-elasticity will influence the fields [11]. Therefore, for points near the edge, there is a challenge to obtain the impact pressure accurately by a numerical model, and minor errors between the experimental values and the numerical ones appear.…”
Section: Parametric Studies Of the Wave Uplift Force With Regular Wavesmentioning
confidence: 99%
“…The time-domain higher-order boundary element method (HOBEM) was applied [9,10] to investigate the hydrodynamic performance of wave slamming when an oscillating wave surge converter (OWSC) interacts with the waves accompanied by the effects of current. Studies have proved that the compressibility of the water, air cushions, air bubbles, and even hydroelasticity can have an influence on the issue, making the process of wave slamming very complex [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other research has revealed different aspects of the flow physics of a nearly rigid plate during flat impact on water. Mayer and Krechetnikov 8 studied the cushion of air trapped under the plate and jetting occurring at the plate edges, called ejecta, using both mathematical analysis and advanced particle image velocimetry (PIV) measurements.…”
Section: Introductionmentioning
confidence: 99%